The Legality of Israel’s Self-Defense Claim of the Strikes on Hamas - Erlangga, Vania Lutfi Safira; Sefriani, Sefriani (Yustisia, 2022)
The attacks by Israel against Palestine, which took place from 10th to 12th May in the Gaza Strip caused massive losses of civilians. Israel claims that the strikes are forms of self-defense in response to previous attacks by Hamas. This study has two objectives: (1) to analyze the arrangements of self-defense in international law and (2) to find out the legality of Israel’s self-defense claim of the strikes on Hamas on May 10-12, 2021. The study was a juridical-normative legal study with a conceptual, historical, and statutory approaches. The results of the study reveal that (1) self-defense is customary international law contains in Article 51 of the United Nations Charter; (2) Israel’s self-defense claim is invalid since it does not comply with Article 51 of the United Nations Charter and elements contained in International Customary Law, such as necessary, proportionality, immediacy, and imminence.